2018
DOI: 10.1038/s41598-018-25976-7
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees consider larval nutritional status rather than genetic relatedness when selecting larvae for emergency queen rearing

Abstract: In honey bees and many other social insects, production of queens is a vital task, as colony fitness is dependent on queens. The factors considered by honey bee workers in selecting larvae to rear new queens during emergency queen rearing are poorly understood. Identifying these parameters is critical, both in an evolutionary and apicultural context. As female caste development in honey bees is dependent on larval diet (i.e. nutrition), we hypothesized that larval nutritional state is meticulously assessed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 81 publications
4
23
0
Order By: Relevance
“…A similar study proved that vitamin supplementation not only improved the percentage of acceptance of queen cells, but also increased the royal jelly production of the workers that attended to the larvae with respect to the controls (Sahinler et al, 2005). A recent work showed that the nutritional status of the larvae is meticulously assessed and used by workers in the selection of larvae for queen rearing (Sagili et al, 2018). Authors performed a series of experiments manipulating the nutritional status of one-day-old larvae by depriving them of brood food for a four-hour period.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A similar study proved that vitamin supplementation not only improved the percentage of acceptance of queen cells, but also increased the royal jelly production of the workers that attended to the larvae with respect to the controls (Sahinler et al, 2005). A recent work showed that the nutritional status of the larvae is meticulously assessed and used by workers in the selection of larvae for queen rearing (Sagili et al, 2018). Authors performed a series of experiments manipulating the nutritional status of one-day-old larvae by depriving them of brood food for a four-hour period.…”
Section: Discussionmentioning
confidence: 83%
“…Nurse bees determine the fate of sibling female larvae by controlling food quantity and quality, resulting in two distinct phenotypes: queens and workers (Sagili et al, 2018). These worker bees have hypopharyngeal and mandibular glands that produce and secrete royal jelly, a complex mixture for the growth and development of young bees (Deseyn & Billen, 2005;Spannhoff et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding of the queen rearing colonies with a feed containing protein, vitamins, and minerals can be said to increase the acceptance rate. According to Gençer et al [14] and Sagili et al [29] , adding pollen or a vitamin mixture to syrup increases the larval acceptance rate.…”
Section: Discussionmentioning
confidence: 99%
“…The larval nutritional state, which is linked to the age of the larva selected for queen rearing, is directly related to the queens weight at emergence (Weaver 1957;Woyke 1971;Sagili et al 2018). Older worker larvae shunted toward queen development emerge with fewer ovarioles and smaller spermathecae, resulting in a reduction in the number of sperm stored after their mating flights (Weaver 1957;Woyke 1971;Dedej et al 1998;Tarpy et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these well-documented studies on caste development and their implications on reproductive potential, it is yet unknown if queen quality is already maximized in naturally reared queens (Sagili et al 2018) or if there are any constraints during ontogenic development that can be artificially overridden to further improve reproductive quality. We hypothesized that the supplementation of the sugar levels in the diet provided to the larva at queen rearing and/or treatment of young larva with JH analogues could provide benefits to the reproductive quality of adult honey bee queens produced by grafting.…”
Section: Introductionmentioning
confidence: 99%